Forecasting land cover transitions in the Upper Bengawan Solo Watershed via CA-Markov modeling - Nada, Firda Maftukhakh Hilmya; Sunariya, Muhammad Iqbal Taufiqurrahman; Nandini, Ryke; Chulafak, Galdita Aruba; Ariseno, Ilyas Ayub; Hadibasyir, Hamim Zaky; Faridah, Rahma Afifah Nur (Journal of Degraded and Mining Lands Management, 2026)
The land cover change analysis in the Upper Bengawan Solo Watershed is crucial because Bengawan Solo is the largest watershed in Java. This study aimed to analyze the spatial and temporal dynamics of land cover change in the Upper Bengawan Solo Watershed during the period 1995-2040. Land cover data obtained from satellite image interpretation were analyzed to identify changes in the periods 1995-2010 and 2010-2025. Furthermore, land cover projections in 2040 were modeled using the CA-Markov method, while the driving factors of land cover change were analyzed using GeoDetector. The analysis showed that settlements, agriculture, and water bodies showed an increasing trend during the periods 1995, 2010, and 2025, while vegetation and bareland showed a decrease. Single-factor analysis showed that slope, soil type, and proximity to rivers and roads had a statistically significant effect on land cover change (p<0.001), although the resulting q statistic value was relatively small. Interaction analysis showed that the combination of factors produced a higher q value than the single factor, especially for the combination of soil and rivers, but the effect remained relatively low. The results of the 2040 projection modeling indicate that settlement and agricultural land cover are expected to continue to increase. Settlements are projected to become the most dominant land cover in the study area, replacing vegetation. If this trend continues without intervention through spatial planning and conservation policies, the ecological balance of the area could potentially be disrupted.